2017
DOI: 10.1044/2016_ajslp-15-0182
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dysarthria Type, Speaking Condition, and Listener Age on Speech Intelligibility

Abstract: Perceptual outcomes vary across speaking modes, even when speakers with dysarthria are grouped according to similar perceptual profiles. Further investigation of interspeaker differences is needed to inform individually tailored intervention approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 38 publications
1
30
0
Order By: Relevance
“…1,10 The finding of only a weak association between vowel space and intelligibility was of interest. In speakers of English, enhanced vowel space has consistently been associated with intelligibility gain 7,8 -and it appears that the same strength of association did not co-occur, at least for the cohort of participants studied in the current investigation. Therefore, the specific acoustic cues that most strongly influence intelligibility in speakers with PD appear to vary cross-linguistically.…”
Section: Speech Intelligibility and Multiple Regression Outcomesmentioning
confidence: 52%
See 3 more Smart Citations
“…1,10 The finding of only a weak association between vowel space and intelligibility was of interest. In speakers of English, enhanced vowel space has consistently been associated with intelligibility gain 7,8 -and it appears that the same strength of association did not co-occur, at least for the cohort of participants studied in the current investigation. Therefore, the specific acoustic cues that most strongly influence intelligibility in speakers with PD appear to vary cross-linguistically.…”
Section: Speech Intelligibility and Multiple Regression Outcomesmentioning
confidence: 52%
“…These findings are consistent with previous studies, which have found that reduced intelligibility is associated with flattened F0 contour at the word level in Mandarin speakers of CP with dysarthria 11 and, furthermore, that compressed VSA is associated with less distinct vowel articulation in speakers of Spanish 3 and English. 7,8 Hence, it is reasonable to conclude that these speech feature might be language-universal features of dysarthria.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in addition to severity of speech impairment, another aspect to be considered in this analysis is the type of dysarthria. The evidence from studies analyzing intelligibility scores in two groups of people with dysarthria, according to type [37] or neurologic disease [15], indicates that the type of the speech disorder could also influence this measure. For example, Tjaden et al [15] described lower sentence intelligibility scores (according to the SIT) for a subgroup of speakers with Parkinson's disease than for a subgroup of speakers with multiple sclerosis, but there were no differences in intelligibility of words measured with the test by Kent et al [3].…”
Section: Discussionmentioning
confidence: 99%